2012
DOI: 10.1016/s1995-7645(12)60010-8
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial potency of the leaf extract of Aspilia africana (Pers.) C.D. Adams

Abstract: The findings show that ethanol extract of A. africana leaf possesses potent antiplasmodial activity which justify the use in ethnomedicine and can be developed in malaria therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…A literature survey revealed that some plants tested in this study had also shown some antiplasmodial and/or antitrypanosomal activities in the previous reports. 5,7,10,[14][15][16]19 Our study showed that A. aspilia, S. alata, F. glumosa and B. buonopozense elicited low in-vitro antiplasmodial activity (IC50 > 20); M. morindiodes was inactive (IC50 > 50) while S. jollyannum showed moderate antiplasmodial activity (10 < IC50 < 20).…”
Section: Resultsmentioning
confidence: 99%
“…A literature survey revealed that some plants tested in this study had also shown some antiplasmodial and/or antitrypanosomal activities in the previous reports. 5,7,10,[14][15][16]19 Our study showed that A. aspilia, S. alata, F. glumosa and B. buonopozense elicited low in-vitro antiplasmodial activity (IC50 > 20); M. morindiodes was inactive (IC50 > 50) while S. jollyannum showed moderate antiplasmodial activity (10 < IC50 < 20).…”
Section: Resultsmentioning
confidence: 99%
“…It is proposed that the presence of alkaloids, triterpenoids, flavonoids, phenolics, and tannins could be responsible for the observed curative antiplasmodial activities of the extract but further experiments are needed to confirm this hypothesis. Some alkaloids that act against malaria parasites inhibit protein synthesis by intercalating with DNA of the parasite (Okokon et al 2008;Christian et al 2012). In addition, flavonoids and tannins have been suggested to act as primary antioxidants or free radical scavengers that can counteract the oxidative damage induced by the malaria parasite (Gautam et al 2011;Kayani et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This was prepared by determining percentage parasitemia and the erythrocytes count of the donor mouse and diluting them with normal saline in proportions indicated by both determinations [10] . Each mouse was inoculated intraperitoneally with infected blood suspension (0.2 mL) containing 1伊10 7 P. berghei parasitized red blood cells.…”
Section: Inoculamentioning
confidence: 99%
“…On Day 3, thin films were made from the tail blood of each mouse. The films were fixed with methanol, stained with 10% Giemsa and parasite density determined by microscopically (Olympus CX 21, Japan) counting the parasitized red blood cells on at least 1 000 red blood cells in 10 different fields [10] .…”
Section: Suppressive Testmentioning
confidence: 99%
See 1 more Smart Citation